THE EFFECT OF LIQUIDITY, LEVERAGE, AND PROFITABILITY ON TAX MANAGEMENT (Case Study of Mining Companies In BEI for The Period 2020-2021) - Rindianti Rindianti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2024)
This study aims to examine the effect of liquidity, leverage, and profitability on tax management. The independent variables used in this study are liquidity, leverage and profitability. While the dependent variable in this study is tax management which is measured using the effective tax rate (ETR). The population in this study amounted to 43 mining companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2021 period. Determination of the sample using purposive sampling and obtained a research sample of 15 mining companies based on certain criteria. The results show that liquidity and leverage have a significant effect on tax management. While profitability has no significant effect on tax management.